(untitled) (Al-Aasar, 2025)
This research paper examines the significance of the Prophet Muhammad’s ﷺ biography as a comprehensive framework for leadership and ethical conduct in the digital age. In an era where digital communication and social media have become dominant tools for interaction, leadership, and knowledge dissemination, humanity faces both unprecedented opportunities and severe ethical challenges. While digital platforms have opened doors for global connectivity, cultural exchange, and educational innovation, they have also created environments that foster misinformation, cyberbullying, hate speech, invasion of privacy, and moral disengagement. These issues highlight an urgent need for ethical guidelines capable of harmonizing technological progress with human dignity. The study argues that the Prophetic model offers timeless guidance for these modern dilemmas. Principles derived from the Prophet’s ﷺ leadership—such as justice, consultation (shūrā), transparency, accountability, and mercy—provide valuable insights for developing a balanced and humane form of digital leadership. Similarly, prophetic ethical values—truthfulness, respect, compassion, responsibility, and safeguarding rights—can be reinterpreted to form the foundation of digital ethics. These values, when contextualized within today’s online realities, help address pressing problems such as fake news, online harassment, irresponsible sharing of information, and the polarization of communities. The paper highlights how the Prophetic model is not confined to historical or theological study, but rather serves as a living paradigm for shaping moral digital citizenship. By linking classical Islamic teachings with contemporary issues, the research underscores the necessity of integrating Prophetic ethics into digital education curricula, institutional policies, online community standards, and global discussions on digital governance. The findings reveal that without an ethical framework, technology risks becoming a tool of exploitation, division, and harm. By contrast, adopting the Prophetic approach to leadership and ethics ensures that the digital space evolves into a platform for truth, justice, and constructive dialogue. The research concludes that the biography of the Prophet ﷺ represents a holistic model of ethical leadership that transcends time and context. It provides not only theoretical guidance but also practical solutions for building a digital culture rooted in human dignity, collective responsibility, and universal values.